THE ROLE OF YOGA IN REDUCING EMOTIONAL STRESS AMONG STUDENTS OF THE COLLEGE OF EDUCATION - Lec. Hayder Abdul Hasan Kareem (Proximus Journal Publishing, 2024)
The current study aims at the role of yoga in reducing emotional behavior among students of the College of Education. Through study, a group of sports were used, such as those that aim to reduce emotional stress, such as (yoga exercises, breathing exercises), interest in maintaining health and increasing the efficiency of educational and productive work, and reducing stress after using yoga exercises for students. The arithmetic mean after the exercises reached (6.770) and the standard deviation (1.140), while the arithmetic mean of the measurement after the exercise was (4.255) and the standard deviation (0.718), while the value of (T) reached (5.0) below the significance level (0.5), which means that there are significant differences in the result after using the breathing exercises, asanas and pranayama, as the students' answers indicated a decrease in the level of emotional stress. Through the results, studyer concluded that practicing yoga reduces emotional stress among students.
Keywords: Yoga; Emotional Stress